Integrated Marketing Communication and its Impact in Enhancing Customer Satisfaction / Field Research in the General Company for Vegetable Oil Industry (Al-Mansour Journal, 2022)
The problem of study diagnosis the reduction in sales in the company of plant oils in some its classes and weakness in differentiation and its reputation at market in spit if having good products with standardized features And lack of customer communication channels، also the company does not have any whole view about the concept of marketing communication، Therefore، This study aimed define to know the type of relationship between the extent of the impact of the integrated marketing communications an independent variable represented the nine dimensions and customer satisfaction as a dependent variable Using a descriptive and analytical approach That is formulated to search premises branched out of the nine major hypotheses، In order to achieve these objectives، the study was applied in the General Company for vegetable oil industry using the descriptive and analytical method with an objective sample of (84) department managers and employees of the company by means of the questionnaire and statistical analysis using statistical methods، and the researcher used analytic and descriptive method with using the statistical analysis program (SPSS-v23) with interviews ، Statistical Methods showed a number of results، the most important active results with a good and positive relation between marketing communication and its dimensions with customer satisfaction، As well as the need for the management of the company investigated to raise awareness of its employees desire to increase the level of satisfaction of customers and thus gain their satisfaction and loyalty .
Keywords: Integrated Marketing; communication; customer satisfaction